On foreign direct investments and the balance of payments constrained growth model in Latin America, 1990-2014 - Alencar, Douglas; Strachman, Eduardo [UNESP]; Seixas Barbosa, Lucio Otavio; Branco Puty, Claudio Alberto Castelo (Assoc Paolo Sylos Labini, 2019)
The aim of this work is to identify whether there was a relationship between foreign direct investment (FDI) and long-term growth in Latin America from 1990 to 2014. Some authors have questioned whether FDI and other capital flows, besides current account results, could constrain economic growth. If FDI and other capital flows are staunched and this is accompanied by capital outflows originated from FDI in previous periods, then it would be possible to experience a balance of payments constraint to economic growth. To test this hypothesis, we slightly amend the Thirlwall and Hussain model and employ the McCombie test for the cases of Brazil, Mexico, and Argentina. We find that the negative effect of primary income remittances on FDI, and even capital inflows through FDI, may curbs growth in the long run.
Keywords: capital flows; economic growth; external constraint